Information security and technology - Ponnappa, B.M (Manas, 2004)
This book is aimed to provide a window and insight into the use of technology in safety and security systems in the present situation. It not only spells out the general approach, principles and guidelines to good security design but also details the basic principles of security management, in regard to all types of security scenarios that involve "Physical Security", "Information Security", "Personal/VIP Security" and the all inclusive mega problems of "Operations Process Security".